Makam Kuno di Kota Rentang: Sejarah Periode Abad Ke-16 M dan Variasi Unik Batu Nisan - Siahaan, Mira Suswati; Ritonga, Sakti; Faturrahman, Muslih (Medan Resource Center, 2024)
This research discusses the ancient tombs in Kota Rentang: history and tombstone variations. The focus of the research is how the history is related to the site in Kota Rentang, how to shape the tombstones, and what the various tombstones in the town explain. The research method used is the historical method, including the stages of data collection through heuristics, verification, interpretation, and historiography. A qualitative approach is used to understand the subject in depth. Data collection techniques include observation, interview, and documentation. Direct observation was conducted by visiting the village in North Sumatra and the archaeological center, interviews were conducted with informants from the North Sumatra archaeological center and the Kota Rentang village community. Documentation is done by studying document sources in the form of manuscripts, photographs, and others. The results showed that the site was a very active trading port around the 11th to 15th centuries AD in the administrative area of Rentang Village, Perak District, Deli Serdang Regency. The history associated with this area is the Aru/Haru Kingdom as mentioned in the Sulalatus Salatin records. Artifacts found date from the 12th to 15th centuries AD, including ancient tombs with headstones from Pasai. Other finds include celadon, pottery and other fragments. The tombs were found in the city's communal cemetery and the scattered tombstones are thought to date back to the 14th century AD and are believed to reflect the morphology of modern tombstones today.